A Comparison of the Efficacy of Dapagliflozin Metformin Versus Sitagliptin Metformin: in Newly Diagnosed Type 2 Diabetes - Afra Ishtiaque, Shahreen Mehmood Khan, Salman Azhar, Mehreen Mehmood, Saira Shahnawaz, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To comparison of the efficacy of dapagliflozin+metformin versus sitagliptin+metformin: in newly diagnosed type 2 diabetes Methodology: In this Randomized Control Trial, we enrolled a total of 180 cases; 90 cases newly diagnosed type 2 diabetes mellitus (HbA1c>6.5) in two equal groups A&B on the basis of computer-generated randomization table. Group A was allotted to the cases 100mg q.d sitagliptin plus 850 mg in addition to 500mg metformin 2 times a day. Patients of Group B were advised for 10mg qd dapagliflozin+500mg metformin 2 times a day for six months. Patients were followed up on monthly basis for any inconvenience. The final follow-up was done on 6th month of treatment. All the patients with poor/non-compliance were excluded from the study. All cases with HbA1c <6.0 were considered as effectively treated patients. Results: Comparison of Efficacy in both groups shows 44(48.9%) in Group A and 31(34.4%) in Group B, the overall efficacy was 41.7%, p-value=0.0.35 showing a significant difference. Conclusion: Dapagliflozin+metformin is significantly higher than sitagliptin+metformin for newly diagnosed type 2 diabetes Keywords: Newly type 2 diabetes, treatment, Dapagliflozin & Metformin Vs Sitagliptin & Metformin